Longitudinal photographic observation of the occurrence of bubbles in pit and fissure sealants Observação fotográfica da ocorrência de bolhas em selantes de fóssulas e fissuras - Renato Herman Sundfeld; Theodore P. Croll; Silvio José Mauro; André Luiz Fraga Briso; Rodrigo Sversut de Alexandre; Maria Lúcia Marçal Mazza Sundefeld (Journal of Applied Oral Science, 2006)
The purpose of this study was to employ photographic evaluation to observe the presence or absence of bubbles in pit and fissure sealants Concise and Prisma Shield, at 7 days, 18 months, 36 months and 11 years after accomplishment of treatment. METHODS: A hematoxylin-based staining solution was applied to the occlusal surface at the study periods, which allowed assessment of the sealing material on the surface. All occlusal surfaces were photographed and the photographs corresponding to each period were subjected to photographic evaluation. RESULTS: There was statistically significant difference only at 18 months, with a significantly higher number of specimens with bubbles for the Prisma Shield sealant compared to the Concise, whereas the groups were similar at all other study periods. On the other hand, separate analysis of subsequent periods of the sealants did not reveal any significant difference. CONCLUSIONS: According to the results of the present longitudinal investigation, it may be concluded that the sealing materials showed that bubbles came into and went out with time. However, this fact did not interfere with its clinical purpose, provided the remaining material covers the expected region of pits and fissures. Avaliação fotográfica para observar a presença ou a ausência de bolhas nos selantes de fóssula e fissuras Concise e Prisma Shield aos 7 dias, 18 meses, 36 meses e 11 anos, após a realização dos selamentos. METODOLOGIA: Foi aplicado na superfície oclusal, em todos os períodos de análise, uma solução corante a base de hematoxilina, que possibilitou a verificação e a avaliação dos materiais seladores presentes nesta superfície. Todas as superfícies oclusais foram fotografadas e as fotografias, correspondentes a cada período em análise, foram submetidas à avaliação fotográfica. RESULTADOS: Verificou-se diferença estatisticamente significativa somente aos 18 meses de análise, com o selante Prisma Shield apresentando um número significativamente maior de bolhas superficiais, que o selante Concise; enquanto que os demais grupos apresentaram-se estatisticamente semelhantes entre si, em todos os outros períodos de análise. Por outro lado, quando os selantes foram analisados isoladamente, nos períodos subseqüentes, não foi observada a presença de diferença estatisticamente significativa. CONCLUSÃO: De acordo com os resultados observados, pudemos verificar que os materiais seladores apresentaram o aparecimento e o desaparecimento de bolhas, fato que não interferiu na finalidade clínica do selamento realizado.